OCCUPATION COMMONLY ASSOCIATED WITH CONTACT DERMATITIS - Elice Wijaya; Luh Made Mas Rusyati; IGK Darmada (E-Jurnal Medika Udayana, 2013)
Occupational skin diseases are a widespread problem. Despite numerous protective mechanisms, the skin remains vulnerable to new irritants found in the workplace. As a result, many workers in different occupations suffer from occupational skin diseases. From the data at Sanglah Hospital in Dermatology Department, it should be noted that there is increasing number of new cases of contact dermatitis in period of January 2000 until December 2005, from 10,16% until 13,36% in the next year and relatively stable in the next four years. Occupations commonly associated with contact dermatitis are agriculture workers, construction workers, dental workers, electronic workers, florists, food workers, hairdressers, haousekeeping personnel, machinist, mechanics, medical workers, office workers, photographers, printers, textile workers.